Animal models of obsessive-compulsive spectrum disorders. (2nd October 2013) - Camilla d'Angelo, Laure-Sophie; Eagle, Dawn M.; Grant, Jon E.; Fineberg, Naomi A.; Robbins, Trevor W.; Chamberlain, Samuel R.
<x content-type="archive" xml:space="preserve">Abstract</x> Obsessive-compulsive disorder (OCD) and related conditions (trichotillomania, pathological skin-picking, pathological nail-biting) are common and disabling. Current treatment approaches fail to help a significant proportion of patients. Multiple tiers of evidence link these conditions with underlying dysregulation of particular cortico-subcortical circuitry and monoamine systems, which represent targets for treatment. Animal models designed to capture aspects of these conditions are critical for several reasons. First, they help in furthering our understanding of neuroanatomical and neurochemical underpinnings of the obsessive-compulsive (OC) spectrum. Second, they help to account for the brain mechanisms by which existing treatments (pharmacotherapy, psychotherapy, deep brain stimulation) exert their beneficial effects on patients. Third, they inform the search for novel treatments. This article provides a critique of key animal models for selected OC spectrum disorders, beginning with initial work relating to anxiety, but moving on to recent developments in domains of genetic, pharmacological, cognitive, and ethological models. We find that there is a burgeoning literature in these areas with important ramifications, which are considered, along with salient future lines of research.